594 Impact of admission hyperglycaemia on heart failure events and mortality in patients with Takotsubo syndrome at long-term follow-up: data from the high-Glucotako investigators. (8th December 2021) - Bergamaschi, Luca; Paolisso, Pasquale; Rambaldi, Pietro; Gatta, Gianluca; Foà, Alberto; Angeli, Francesco; Fabrizio, Michele; Casella, Gianni; Barbieri, Michelangela; Galiè, Nazzareno; Marfella, Raffaele; Pizzi, Carmine; et al.
Abstract: Aims: As known, Takotsubo Syndrome (TTS) can occur during stressful events that result in sympathetic overactivity. No studies have investigated the sympathetic activity and long-term prognosis in patients with TTS and admission hyperglycaemia vs. normoglycaemia. Moreover, whether hyperglycaemia may serve as a metabolic trigger to unbalance the sympathetic system axis as well as through over-inflammation is not fully understood. To investigate admission hyperglycaemia effects on the sympathetic system and long-term prognosis in Takotsubo syndrome (TTS). Methods and results: In this multicentre study, we screened 4783 patients undergoing coronary angiography within the first 72 h of hospitalization for suspected acute coronary syndrome between January 2015 and January 2018. All enrolled patients met the InterTAK diagnostic criteria proposed in the European Society of Cardiology position statement for the diagnosis of TTS. Exclusion criteria encompassed patients with previous myocardial infarction, TTS events, or chronic kidney or liver disease. Patients with TTS were divided into those with hyperglycaemia vs. those with normoglycaemia according to a cutoff admission blood glucose value of 140 mg/dl. Sympathetic activity was assayed by blood values of norepinephrine and 123I-labelled metaiodobenzylguanidine (MIBG) cardiac scintigraphy with late heart-to-mediastinum ratio (H/Mlate) and washout rate (WR), performed in 30 patients who did not present any contraindication to the examination, evaluated at baseline and at follow-up. Similarly, systemic inflammatory markers [C-reactive protein (CRP), white blood cell count (leukocytes and neutrophils), tumour necrosis factor-alpha (TNF-a)] and B-type natriuretic peptide (BNP) were assessed. Prespecified endpoints [heart failure (HF) and all-cause deaths] were assessed at long-term follow-up (12 and 24 months). At hospitalization, TTS patients with hyperglycaemia ( N = 28) vs. those with normoglycaemia ( M = 48) had significantly higher levels of inflammatory markers and B-type natriuretic peptide and lower left ventricular ejection fraction. Admission glucose values were correlated with norepinephrine levels ( R 2 = 0.39; P = 0.001). In 30 patients with TTS, 123I-MIBG cardiac scintigraphy showed lower late heart-to-mediastinum ratio values in the acute phase ( P < 0.001) and at follow-up ( P < 0.001) in those with hyperglycaemia. Patients with hyperglycaemia had higher rates of HF ( P < 0.001) and death events ( P < 0.05) after 24 months. In multivariate Cox regression analysis, hyperglycaemia ( P = 0.008), tumour necrosis factor-alpha ( P = 0.001), and norepinephrine ( P = 0.035) were independent predictors of HF events. Conclusions: Patients with TTS and hyperglycaemia exhibit sympathetic overactivity with a hyperglycaemia-mediated proinflammatory pathway, which could determine a worse prognosis during follow-up.